Preston lee's read & write english lesson 1 ebook 40 for ukrainian speakers. - Lee, Preston (Smashwords Edition, 2020)
40 interesting lessons to help the learner master English! Level: Intermediate - Students should have a basic knowledge of reading, writing and grammar. Application: Self-learning & Classroom Have fun and learn English the best way! This workbook has been written for all ages, children and adults alike. This workbook features: - 40 excellent lessons with everyday topics - 400 important words used in daily life - 40 Readings with everyday topics - 40 fun worksheets for easy learning - Commonly used grammar tenses - Step-by-step grammar development - Vocabulary words include Ukrainian translations The words in this book are taken from the best-selling book, Preston Lee's Beginner English 100 Lessons. A great book to be used with, Preston Lee's Conversation English Lesson 1 - 40. Preston Lee's Beginner English is the absolute best way to learn English. Written by ESL specialists, Kevin Lee and Matthew Preston have taught English as a Second Language for over 20 years around the world.